The Fraud Triangel Approach: Detecting Fraudulent Behavior in Business Finance in Sidoarjo: Pendekatan Fraud Triangel: Mendeteksi Prilaku Kecurangan Pada Keuangan Bisnis Di Sidoarjo - Nihlatul Qudus Sukma Nirwana (Academia Open, 2023)
Fraud that occurs in MSME players today is increasingly diverse. Fraud can take the form of financial statement fraud, mixing personal finances with business finances or dishonesty in running a business. This causes a prolonged dilemma for MSME actors in managing business income. Many MSMEs have not been able to manage good financial reports. This Research Objective is used to gain a deeper understanding of the behavior and detection of fraud that occurs in Micro, Small and Medium Enterprises (MSMEs) based on the Fraud Triangle Theory and the efforts made by MSMEs in preventing and detecting fraud early. The type of sample experiment research used is the random method. The method of collecting information through direct observation and questions, FGDs and the technique of using documentation in the data collection process. The data analysis approach involves the steps of data reduction, data presentation and data verification. The results of the analysis explain that MSME actors do not all carry out financial statement management and still carry out a lot of fraud. The implications of this research contribute to the understanding of fraud, especially by forensic accountants, auditors, fraud examiners and anti-fraud examiners who are used to see fraud in MSMEs. Highlights : Fraud in MSMEs is multifaceted, encompassing financial statement manipulation and unethical business practices. Research aims to understand fraud behavior using the Fraud Triangle Theory and explore MSME efforts in fraud prevention. Utilizes random sampling and data collection methods like direct observation, FGDs, and documentation to gather comprehensive insights. Keywords : Fraud Triangel, Financial Statements, Fraudulent Behavior and MSMEs